Overexpression of tRNA m7G modification methyltransferase complex promotes the biosynthesis of triterpene in yeast - Ma, Mengyu; Wang, Jun; Tan, Zhengwei; Liang, Xiqin; Fan, Bengui; Li, Lei; Liang, Huizhen; An, Tianyue; Wang, Guoli (Frontiers in Microbiology, 2025)
BackgroundThe sustainable production of valuable compounds using microbial cell factories is an effective approach, yet further metabolic engineering strategies are needed to enhance their biosynthetic potential. Recent studies suggest that RNA modifications can influence cellular metabolism, but their role in metabolic engineering remains largely unexplored.MethodsThe production of squalene and lupeol in different yeast strains was detected by gas chromatography-mass spectrometry (GC-MS) equipment. Transcriptomic analysis was performed to identify metabolic changes associated with the epigenetic modification. The transcriptional and translational expression of targeted genes were determined by real-time quantitative polymerase chain reaction and western blotting, respectively. The mRNA stability of targeted genes was measured by mRNA decay assay.ResultsIn this study, the overexpression of Trm8 and Trm82 complex, mediating the tRNA 7-methylguanosine (m7G) modification in yeast, significantly increased the production of squalene in CEN.PK2-1C. Transcriptome analysis indicated that Trm8/Trm82 overexpression upregulated the expression levels of genes involved in amino acid synthesis, glycolysis, and tricarboxylic acid cycle, and the enhanced glycolysis, upstream of acetyl-CoA biosynthesis, might be responsible for the promoted biosynthesis of squalene. Further investigation demonstrated that Trm8/Trm82 complex could increase the production of squalene and lupeol in engineered yeast.ConclusionThese findings indicate that tRNA m7G modification can regulate central metabolism and enhance terpenoid biosynthesis. This study provides new insights into RNA modifications as a potential metabolic engineering strategy for improving the production of high-value compounds.